Laparoscopic Management of Synchronous Bilateral Ovarian Torsion in a Neonate - Alkan, Murat; Elbek, Ali; Evruke, Cuneyt; Memec, Ahmet Eray; Ozkan, Bulent Aziz; Sucak, Hatice Gülin; Erkan, Ozgur Talat (Journal of Neonatal Surgery, 2015)
Synchronous bilateral ovarian torsion is an uncommon entity of which both ovaries twist at the same time or observed twisted during the surgical intervention. Herein, we present a neonate with bilateral ovarian torsion, which successfully managed by laparoscopic approach.